Growth Response of Phalaenopsis Seedling on Various Concentrations of Hyponex Leaf Fertilizer - R. Rosmaladewi; R. Rahmawati; Marlina Mustafa (Universitas Sembilanbelas November Kolaka, 2022)
The aim of the study was to determine and analyze the effect of Phalaenopsis seedling growth at various concentrations of Hyponex foliar fertilizer. This study was conducted in Cempalagi Village, Tempe Sub-district, Wajo Regency. By using a randomized block design consisting of five concentrations of hyponex fertilizer, namely: 1.0 g/liter of water, 2.0 g/liter of water, 2.5 g/liter of water, 3.0 g/liter of water and 3.5 g/liter of water. Results of study showed that the concentration of hyponex fertilizer at 2.5g/liter of water obtained the best results on leaf number, leaf length, leaf thickness, root number and root length of Phalaenopsis orchids